Cultural variation in individuals' responses to incivility by perpetrators of different rank: The mediating role of descriptive and injunctive norms. (20th December 2017) - Moon, Chanki; Weick, Mario; Uskul, Ayse K.
Abstract: The present research sought to establish how cultural settings create a normative context that determines individuals' reactions to subtle forms of mistreatment. Two experimental studies ( n = 449) examined individuals' perceptions of high‐ and low‐ranking individuals' incivility in two national (Study 1) and two organizational (Study 2) cultural settings that varied in power distance. Consistent across studies, the uncivil actions of a high‐ranking perpetrator were deemed more acceptable than the uncivil actions of a low‐ranking perpetrator in the large power distance cultural settings, but not in the small power distance cultural settings. Differing injunctive norms (acceptability), but not descriptive norms (perceived likelihood of occurrence), contributed to cultural variations in the level of discomfort caused by incivility. In addition, perceptions of descriptive and injunctive norms coincided, but differed markedly in their associations with discomfort. We discuss the practical and theoretical implications of these findings.